Interannual Variability in the Source Location of North African Dust Transported to the Amazon. Issue 10 (16th May 2022) - Barkley, Anne E.; Pourmand, Ali; Longman, Jack; Sharifi, Arash; Prospero, Joseph M.; Panechou, Kathy; Bakker, Natalie; Drake, Nick; Guinoiseau, Damien; Gaston, Cassandra J.
Abstract: African dust is transported to South America (SA) every winter and spring. Hypotheses suggest that either Western or Central North Africa (e.g., Bodélé Depression) is the main source of transported dust, yet these notions remain largely untested with geochemical data. Using 2 years of isotopic measurements (strontium and neodymium) of African dust collected in SA integrated into a statistical model, we identified strong interannual variability in dust source region. Central North Africa supplied 44% of long‐range transported dust in winter 2016 while the Western region accounted for 53% of dust in winter 2014. We propose the variability is due to differences in the strength of the Libyan High and precipitation over the Gulf of Guinea and Atlantic Ocean between the 2 years. Our findings can improve constraints of dust nutrient deposition and predictions of how changes in climate impact the source and magnitude of dust transported to the Amazon. Plain Language Summary: Dust is blown from North Africa to the Amazon and the western Atlantic Ocean in winter and spring. Identifying the area within North Africa where dust originates is the subject of intense debate, with leading hypotheses disagreeing on whether the Bodélé Depression (Central North Africa) or Western North Africa provide dust that fertilizes the Amazon. Here, we present a more nuanced hypothesis: dust from both the Central and Western North African dust source regions are important with the dominate source depending on the prevailing meteorological factors and precipitation patterns. Our hypothesis is supported by isotopic fingerprinting that was used to determine the source area of dust transported to South America (SA). We then integrated our data into a statistical model, which quantifies the proportion of dust from each North African region that contributes to the dust we collected in SA. Because dust source location dictates the amount and solubility of associated nutrients, changes in dust source impacts nutrient deposition to the Amazon and Tropical Atlantic Ocean. Additionally, identifying the factors that control dust source location can provide clues into how past and future changes in climatological conditions affect dust transport. Key Points: Western North African dust sources dominated transport to the Amazon in winter 2014 while Central dominated in winter 2016 Interannual variability in dust source is likely due to differences in meteorology and precipitation Sources of North African dust transported to the Atlantic Ocean and Amazon could change as climate changes altering nutrient deposition